Predictors of lower-limb arterial occlusion pressure across commonly used cuff widths - Wedig, Isaac J.; Lennox, Isaac M.; Petushek, Erich J.; Durocher, John J.; McDaniel, John; Elmer, Steven J. (Frontiers in Physiology, 2025)
We compared predictors of lower-limb arterial occlusion pressure (AOP) across commonly used blood flow restriction (BFR) cuff widths (11, 13, 18 cm) and developed prediction equations to estimate AOP for each cuff. Participants (n = 116) underwent measurements of thigh circumference (TC), systolic (SBP) and diastolic (DBP) blood pressure, and AOP was assessed using Doppler ultrasound in a seated position. Multiple linear regression models with commonality analysis and mixed-effects models were used to identify and compare predictors of AOP between each cuff. LASSO regression with bootstrap resampling was used to develop and internally validate prediction equations. TC, SBP, DBP, age, and sex explained 60%–70% of total variance in AOP, with greater predictive power in narrower cuffs. As cuff width increased, TC uniquely accounted for less (36%, 26%, 11% for 11, 13, 18 cm, respectively) and SBP uniquely accounted for more (2%, 6%, 12% for 11, 13, 18 cm, respectively) variance. A cuff width × TC interaction indicated that limb size had greater influence on AOP with narrower cuffs. In contrast, the relationship between SBP and AOP remained stable across cuff widths. Prediction equations demonstrated good predictability and calibration, with limits of agreement ranging from ±18.4 to ±28.6 mmHg and statistical equivalence between predicted and measured AOP. Internal validation showed minimal overfitting. These findings highlight the importance of accounting for cuff width in BFR pressure prescription, with narrower cuffs requiring consideration primarily of TC, and wider cuffs requiring consideration of both TC and SBP. These cuff-specific equations may offer a practical alternative to direct AOP measurement.